2008
DOI: 10.1142/s1793292008001337
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Intrinsic and Extrinsic Toxicity of Silica Nanoparticles and Its Impact on Marine Organisms

Abstract: The intrinsic and extrinsic toxicity of SiO 2 nanoparticles (Aerosil OX50, φ ∼ 40 nm) are investigated with a comparison to the particles in micron size (SiO 2 gel, φ ∼ 1.5 µ m). Nanoparticles potentially functioned as a carrier of harmful substances transfer was assessed by examining the surface adsorption behavior of the nanoparticles towards γ-picoline (4-methylpyridine), recognized as one type of the marine pollutants, as well as the penetration behavior of the nanoparticles towards a typical marine macro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…56 Zhang et al found that the large surface area of silica nanoparticles results in a high adsorption capability and allows the particles to participate in possible toxic carrier activities toward marine organisms. 57 Therefore, the use of a small amount of nanoparticles in this study would greatly reduce their potential adverse environmental impacts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56 Zhang et al found that the large surface area of silica nanoparticles results in a high adsorption capability and allows the particles to participate in possible toxic carrier activities toward marine organisms. 57 Therefore, the use of a small amount of nanoparticles in this study would greatly reduce their potential adverse environmental impacts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This may increase the toxicity to marine organisms that feed on plankton in the littoral and limnetic zones. 66,67 Furthermore, Monikh et al suggest the utilization of detailed experimental protocols as per OECD TG No. 318 along with kinetic parameters for better assessment of the potential toxicity of engineered nanomaterials released in the environment.…”
Section: Nsio 2 : Environmental Risk Implicationsmentioning
confidence: 99%
“…12,16,17 Indeed, the fate and behavior of nanoparticles in the aquatic environment are not absolute and are affected by several parameters such as the presence of organic matter, concentration, the nanoparticle distribution, agglomeration size/de-agglomeration and solubility, etc., 13,18 Zhang et al examined the interaction between SiO 2 nanoparticles and γ-picoline. 19 They identified high adsorption properties of SiO 2 nanoparticles that made them toxic carriers for γ-picoline. Thus, the impact of nanoparticles on ecosystems as well as interactions across ecosystem boundaries merits special attention.…”
Section: Introductionmentioning
confidence: 99%
“…, 13,18 Zhang et al examined the interaction between SiO 2 nanoparticles and γ-picoline. 19 They identified high adsorption properties of SiO 2 nanoparticles that made them toxic carriers for γ-picoline. Thus, the impact of nanoparticles on ecosystems as well as interactions across ecosystem boundaries merits special attention.…”
Section: Introductionmentioning
confidence: 99%